Breakthrough technologies and expansion of the infrastructure of innovation development - Беляков, Виктор Николаевич; Козинец, Виктор Павлович; Стелюк, Барбара Борисівна (Eastern-European Journal of Enterprise Technologies, 2012)
It was shown the factors of innovative scientific and technological development that improve the entrepreneurial capacity of business entities. It was highlighted the features of the clustering management technology and expansion of regional infrastructure for innovation development of Ukraine